Peace and the public purse : (Lynne Rienner Publishers, Inc., 2007)
In the aftermath of violent conflict, how do the economic challenges of state building intersect with the political challenges of peace building? How can the international community help lay the fiscal foundations for a sustainable state and a durable peace? "Peace and the Public Purse" examines these questions, lifting the curtain that often has separated economic policy from peace implementation. Drawing on recent experiences in Afghanistan, Bosnia, Cambodia, East Timor, Guatemala, Palestine, and Uganda, the authors bring to life a key dimension of how both peace and states are built. The book explores how the economic challenges of state building intersect with the political challenges of peace building in the aftermath of violent conflict.